Seasonality of gestational diabetes mellitus: a South Australian population study. Issue 1 (18th October 2016) - Verburg, Petra E; Tucker, Graeme; Scheil, Wendy; Erwich, Jan Jaap H M; Dekker, Gus A; Roberts, Claire T
Abstract : Objective: To investigate whether there is a seasonal variation in the incidence of gestational diabetes mellitus (GDM). Research design and methods: This retrospective cohort study of 60 306 eligible South Australian live-born singletons during 2007–2011 recorded in the South Australian Perinatal Statistics Collection (SAPSC) examined the incidence of GDM in relation to estimated date of conception (eDoC). Fourier series analysis was used to model seasonal trends. Results: During the study period, 3632 (6.0%) women were diagnosed with GDM. Seasonal modeling showed a strong relation between GDM and eDoC (p<0.001). Unadjusted and adjusted models (adjusted for maternal age, body mass index (BMI), parity, ethnicity, socioeconomic status, and chronic hypertension) demonstrated the presence of a peak incidence occurring among pregnancies with eDoC in winter (June/July/August), with a trough for eDoc in summer (December/January/February). As this was a retrospective study, we could only use variables that had been collected as part of the routine registration system, the SAPSC. Conclusions: This study is the first population-based study to demonstrate a seasonal variation for GDM. Several maternal lifestyle and psychosocial factors associated with seasonality and GDM may be influential in the pathophysiologic mechanisms of GDM. Ambient temperature, physical activity, nutrient intake, and vitamin D levels may affect maternal physiology, and fetal and placental development at the cellular level and contribute to the development of GDM. The mechanisms underlying these possible associations are not fully understood and warrant further investigation.